2018
DOI: 10.3168/jds.2018-14759
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of selected mastitis pathogens during the dry period

Abstract: We aimed to evaluate the elimination of 4 different mastitis pathogens, Streptococcus agalactiae, Mycoplasma bovis, Staphylococcus aureus, and Streptococcus uberis, from infected udder quarters during the dry period using quantitative PCR. The second purpose of this study was to evaluate the association between milk haptoglobin (Hp) concentration and the presence of udder pathogens (Strep. agalactiae, Staph. aureus, M. bovis, and Strep. uberis) in udder quarter milk samples before and after dry period. Aseptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The prevalence of milk samples with no pathogen DNA in STER (58.70%) and DHI (49.30%) resembled the findings of Narayana et al [ 21 ], who performed bacterial cultures on 46,900 quarter-level samples of Canadian Holsteins and reported 54.5% uninfected samples. Using qPCR for the identification of four pathogens, Timonen et al [ 25 ] observed that pathogen DNA was absent in 62.5% of quarter milk samples collected from 133 Holsteins. Moreover, the prevalence of pathogens observed in the present paper ( Table 4 ) agrees with the results of studies that investigated pathogen prevalence in clinically healthy cows [ 21 , 25 ] or in cows with detected or suspected mastitis [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of milk samples with no pathogen DNA in STER (58.70%) and DHI (49.30%) resembled the findings of Narayana et al [ 21 ], who performed bacterial cultures on 46,900 quarter-level samples of Canadian Holsteins and reported 54.5% uninfected samples. Using qPCR for the identification of four pathogens, Timonen et al [ 25 ] observed that pathogen DNA was absent in 62.5% of quarter milk samples collected from 133 Holsteins. Moreover, the prevalence of pathogens observed in the present paper ( Table 4 ) agrees with the results of studies that investigated pathogen prevalence in clinically healthy cows [ 21 , 25 ] or in cows with detected or suspected mastitis [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using qPCR for the identification of four pathogens, Timonen et al [ 25 ] observed that pathogen DNA was absent in 62.5% of quarter milk samples collected from 133 Holsteins. Moreover, the prevalence of pathogens observed in the present paper ( Table 4 ) agrees with the results of studies that investigated pathogen prevalence in clinically healthy cows [ 21 , 25 ] or in cows with detected or suspected mastitis [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that cows receiving antimicrobial dry cow therapy (aDCT) had a significantly higher cure rate (86.6%) than cows that did not receive antimicrobial treatment (59.2%), confirming the importance of treating udder disease at this time [15]. Similarly, an Estonian study reported extremely high elimination rates of mastitis pathogens during the dry period when cows were treated with cloxacillin-containing dry cow intramammary injectors, namely 100% for Streptococcus uberis and 93.6% for Staphylococcus aureus [12]. While the antimicrobial treatment of infected cows is therefore essential, a number of countries have attempted to implement a more prudent use of antimicrobials in the dairy sector and some countries such as Finland, the Netherlands and Denmark have effectively banned the prophylactic use of antimicrobials at drying off for all cows (blanket dry cow therapy) if their infection status is not known [16,17,18].…”
Section: Introductionmentioning
confidence: 96%
“…Since the introduction of the five-point plan for mastitis prevention in 1966 [9], the use of antimicrobial dry cow therapy at drying off in all cows has been a routine herd health procedure worldwide. Indeed, treating cows with persistent high somatic cell counts (SCC) over an extended period with antimicrobials is often the best way to ensure bacterial cure [10,11,12,13,14]. Dairy cows are often already infected with mastitis pathogens at the time of drying off, as shown by, for example, Kiesner and colleagues in a German study where 38.4% of 250 cows from five different farms had intramammary infections (excluding minor pathogens) at this time [15].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of IMI increases with teat end contamination, incomplete formation of the keratin plug in the teat, and immunosuppression before and after calving (Bradley and Green, 2004). As well, most new clinical and subclinical infections caused by S. uberis in early lactation originate in the dry period, when risk of infection is increased because of a decrease in immunological defenses and greater exposure to environmental microorganisms (Timonen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%